REPLACEMENT VALUE OF SUPER SOSAT MILLET FOR MAIZE IN GROUNDNUT CAKE BASED DIETS ON THE GROWTH PERFORMANCE AND CARCASS QUALITY OF BROILER CHICKENS - Bello, A.T.; Abubakar, M.; Doma, U.D.; Sani, U.M.; Garba, S.I.; Alhassan, N.M.; Bot, M.H. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The experiment was conducted to evaluate the response of broiler chickens fed Super SOSAT (SSM) pearl millet to replace maize as a source of energy in groundnut cake based broiler chickens diets. Three hundred broiler chicks were randomly allotted to five dietary treatments in replicates of three containing 20 birds each in a completely randomized design. In the trial, Super SOSAT millet replaced maize at 0, 25, 50, 75 and 100% levels. Feed and water were served ad lib and the experiment lasted for 42 days. Results showed that at both the starter and overall phases, no influence of SSM was observed on performance indices. At the starter phase, daily feed intake (DFI) ranged from 77.35g (diet 4) to 86.47g (diet 2), while daily weight gain (DWG) varied from 29.52g (diet 2) to 39.21g (diet 1). At the overall phase, DFI ranged from 105.80 g (diet 4) to 118.43 g (diet 2), while daily weight gain (DWG) varied from 37.46 g (control diet) to 42.30 g (diet 2). Similarly, feed conversion ratio (FCR) ranged between 2.67 (diet 3) and 3.12 on diet 2. However, at the finisher phase DWG and FCR were significantly (P<0.05) higher for diets with super SOSAT millet compared to the control. The results of carcass characteristics shows that except for lung weight, head weight and weight of the small intestine, no parameter was significantly (P>0.05) influenced treatments. Live weight of birds was between 1.94 kg on diet 1 to 2.14 kg on diet 3, plucked weight from 1.70 kg (diet 1) to 1.87 kg (diets 2 and 3), eviscerated weight from 1.30 to 1.42 kg on diets 1 and 2 respectively. Carcass weight ranged from 1.22 kg (diets 1 and 4) to 1.29 (diet 3), while the birds dressed between 59.14 – 63.78 % on diets 3 and 1 respectively. The cost benefit analysis of broiler chickens fed the experimental diets showed a progressive decrease in overall feed cost per kg gain from N348.96 (diet 1) to N275.51 (diet 5). Consequently, cost savings increased gradually from N24.04 for diet 1 to N73.45 for those on diet 5. The results of the current study showed that Super SOSAT millet can completely replace maize in broiler chickens’ diets without any deleterious effect on growth performance and carcass characteristics.However, based on the DWG of 40.24g and the least feed cost/kg gain of N275.51 for broiler chickens in diet 5 compared to the others, it is recommended for broiler chickens.